A cross-sectional study on the symptoms of depression in dental students in Kerbela - Athraa A Abass; Radhwan Alhashem; Ghazwan Alhashem (Technium BioChemMed, 2024)
Doktorchik C, Patten S, Eastwood C, et al. Validation of a case definition for depression in administrative data against primary chart data as a reference standard. BMC Psychiatry. 2019;19(1):9. doi:10.1186/s12888-018-1990-6 Mancuso E, Sampogna G, Boiano A, Della Rocca B, Di Vincenzo M, Lapadula MV, Martinelli F, Lucci F, Luciano M. Biological correlates of treatment resistant depression: a review of peripheral biomarkers. Front Psychiatry. 2023 Oct 24; 14:1291176. doi: 10.3389/fpsyt.2023.1291176. PMID: 37941970; PMCID: PMC10628469. Machado MO, Veronese N, Sanches M, et al. The association of depression and all-cause and cause-specific mortality: an umbrella review of systematic reviews and meta-analyses. BMC Med. 2018;16(1):112. doi:10.1186/s12916-018-1101-z Mancuso E, Sampogna G, Boiano A, Della Rocca B, Di Vincenzo M, Lapadula MV, Martinelli F, Lucci F, Luciano M. Biological correlates of treatment resistant depression: a review of peripheral biomarkers. Front Psychiatry. 2023 Oct 24; 14:1291176. doi: 10.3389/fpsyt.2023.1291176. PMID: 37941970; PMCID: PMC10628469. Ménard C, Hodes GE, Russo SJ. Pathogenesis of depression: Insights from human and rodent studies. Neuroscience. 2016; 321:138-162. Kieling C, Buchweitz C, Caye A, Silvani J, Ameis SH, Brunoni AR, Cost KT, Courtney DB, Georgiades K, Merikangas KR, Henderson JL, Polanczyk GV, Rohde LA, Salum GA, Szatmari P. Worldwide Prevalence and Disability From Mental Disorders Across Childhood and Adolescence: Evidence From the Global Burden of Disease Study. JAMA Psychiatry. 2024 Apr 1;81(4):347-356. doi: 10.1001/jamapsychiatry.2023.5051. PMID: 38294785; PMCID: PMC10831630. Theriault KM, Rosenheck RA, Rhee TG. Increasing emergency department visits for mental health conditions in the United States. J Clin Psychiatry. 2020;81(5):5456. Patel JS, Oh Y, Rand KL, Wu W, Cyders MA, Kroenke K, Stewart JC. Measurement invariance of the patient health questionnaire-9 (PHQ-9) depression screener in U.S. adults across sex, race/ethnicity, and education level: NHANES 2005-2016. Depress Anxiety. 2019 Sep;36(9):813-823. doi: 10.1002/da.22940. Epub 2019 Jul 29. PMID: 31356710; PMCID: PMC6736700. Sun Y, Fu Z, Bo Q, Mao Z, Ma X, Wang C. The reliability and validity of PHQ-9 in patients with major depressive disorder in psychiatric hospital. BMC Psychiatry. 2020;20(1):474. doi:10.1186/s12888-020-02885-6 Van Der Zwaan GL, Van Dijk SE, Adriaanse MC, et al. Diagnostic accuracy of the Patient Health Questionnaire-9 for assessment of depression in type II diabetes mellitus and/or coronary heart disease in primary care. J Affect Disord. 2016; 190:68-74. Basudan S, Binanzan N, Alhassan A. Depression, anxiety and stress in dental students. Int J Med Educ. 2017; 8:179. Alhashem G, Abbas A a. R, Ali S a. J, Almhanna A. Prevalence of depression among Iraqi dentistry students during COVID-19 returning to onsite learning: A cross-sectional study. Eur Psychiatry. 2023;66(S1): S149-S150. doi: 10.1192/j.eurpsy.2023.369 Rehnisch C, Feußner O, Klima I, et al. Depressive symptoms in dentistry students—prevalence, risk factors and resilience factors. Dtsch Zahnärztliche Z. 2021;3(6):266-275. Lu N, Sun H, Yu J, et al. Glucagon-like peptide-1 receptor agonist Liraglutide has anabolic bone effects in ovariectomized rats without diabetes. Holscher C, ed. PLOS ONE. 2015;10(7): e0132744. doi: 10.1371/journal.pone.0132744 Zhao L, Han G, Zhao Y, et al. Gender differences in depression: evidence from genetics. Front Genet. 2020; 11:1145. Kang J, Jang SN, Kim HS. What differentiates suicidal ideation from depressive symptoms amongst Korean young adults aged 20-39 years? Int Rev Psychiatry. 2024 Jun- Aug;36(4-5):315-325. doi: 10.1080/09540261.2024.2311102. Epub 2024 Feb 8. PMID: 39470081. Liu X, Gao X, Ping S. Post-1990s college student’s academic sustainability: the role of negative emotions, achievement goals, and self-efficacy on academic performance. Sustainability. 2019;11(3):775.